Vegetarian Dietary Patterns for Adults: A Position Paper of the Academy of Nutrition and Dietetics - Raj, Sudha; Guest, Nanci S.; Landry, Matthew J.; Mangels, A. Reed; Pawlak, Roman; Rozga, Mary (Journal of the Academy of Nutrition and Dietetics, 2025)
It is the position of the Academy of Nutrition and Dietetics that, in adults, appropriately planned vegetarian and vegan dietary patterns can be nutritionally adequate and can offer long-term health benefits such as improving several health outcomes associated with cardiometabolic diseases. Vegetarian dietary patterns exclude meat, poultry, and seafood, and vegan dietary patterns exclude all foods of animal origin. Registered dietitian nutritionists (RDNs) and nutrition and dietetics technicians, registered (NDTRs) play a pivotal role in providing meal-planning strategies and evidence-based nutrition information to clients currently following vegetarian or vegan dietary patterns or who may benefit from and express interest in following vegetarian or vegan dietary patterns. RDNs and NDTRs can work with their clients to create tailored, lifestyle-oriented, nutritionally balanced, and culturally suitable vegetarian and vegan dietary patterns that optimize health benefits while reducing concerns about nutrient inadequacies. Adults follow vegetarian and vegan dietary patterns for various reasons. The aim of this position paper is to inform health care practitioners, including RDNs and NDTRs, about the evidence-based benefits and potential concerns of following vegetarian and vegan dietary patterns for different populations of nonpregnant, nonlactating adults. This position paper is supported by current evidence, including several systematic reviews. As leaders in evidence-based nutrition care, RDNs and NDTRs should aim to support the development and facilitation of vegetarian and vegan dietary patterns and access to nutrient-dense plant-based meals. Promoting a nutrient-balanced vegetarian dietary pattern on both individual and community scales may be an effective tool for preventing and managing many diet-related conditions. This position was approved in January 2025 and will remain in effect until December 31, 2032.